Komisi Pemberantasan Korupsi sebagai Tata Konstitusional Abnormal dan Implikasi Yuridis Putusan Mahkamah Konstitusi Nomor 36/PUU-XV/2017 - Titon Slamet Kurnia (Jurnal Konstitusi, 2020)
This article expresses the author’s view to disagree with the existence of the KPK and its supporting Constitutional Theory. This article is based on classical model of the trias politica theory and suggests that the existence of executive bodies should conform with the prescription of unitary executive theory. According to the unitary executive theory, the president should have the power to appoint and remove any executive official exclusively. This norm is based on the status of the president as the Chief Executive. According to this notion, the KPK, as independent agency, is unconstitutional. In line with the Constitutional Court Decision No. 36/PUU-XV/2017, qualifying the KPK as executive, our abnormal constitutional order, with the existence of the KPK, should be normalized in accordance with the unitary executive theory.